Predictors of health-related quality of life among Libyan patients infected with the hepatitis C virus - Ibrahim Adam, Samia; Md Said, Salmiah; Daw, Mohamed Ali; Khalid, Bahariah; Kadir Shahar, Hayati (Community Health Society Malaysia, 2017)
Background: The health-related quality of life (HRQL) is an important health outcome for chronic hepatitis C (CHC) patients. This study explored the predictors of HRQL of CHC patients in Libya. The objective of the study was to identify the common predictors of physical and mental component scores (PCSs and MCSs) of HRQL of CHC patients in Tripoli Medical Center in Libya. Materials and Methods: A cross section study was conducted among 100 CHC patients randomly selected from the infections and gastroenterology clinics in Tripoli Medical Center in Libya. Well validated and self-administered questionnaire was used. Data analysed using bivariate and multivariate statistical tests. Result: In a bivariate analysis, age, gender, work status, other medical disease(s) and treatment(s), virological response, adherence to ribavirin treatment, knowledge of HC infection, self-efficacy, and social support significantly (p < 0.05) predicted both the physical and mental components of the HRQL. However, after controlling for the independent variables and covariates in multivariate analysis of covariance (MANCOVA), it was found that only gender significantly (p < 0.025) predicted both the physical and mental components of HRQL, while the virological response and social support could only predict the mental components of the HRQL significantly. Conclusion: This study has important clinical implications as identification of predictors of the physical and mental components of the HRQL for patients with CHC allows for efficient clinical therapy and counselling for these patients before and during the course of treatment.